2020
DOI: 10.17645/si.v8i3.3531
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Spanning in Sport for Development: Opening Transdisciplinary and Intersectoral Perspectives

Abstract: We can no longer claim that academic interest in the area of sport and social inclusion is lacking. Dedicated books, special issues, commissioned reports, and landmark articles on the topic of social inclusion and sport have been produced by devoted scholars. The same can be said for the burgeoning area of sport for development and peace. These relatively young academic fields seem to be struggling to create new fundamental theoretical insights about how organized sport can both act as an inclusive space and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Second, with respect to the limited translation of sport outcomes in other life domains, a stronger involvement of the distal ecological systems [32] for supporting youth educational path outside sport should be considered. Several studies reported the benefit of a multi-stakeholder approach in sport, resulting in "economy of effort", namely, better use of resources and competencies for supporting youth [35,[45][46][47]. The multi-stakeholder approach, thus, should be intensified, especially when working with vulnerable youth.…”
Section: Discussionmentioning
confidence: 99%
“…Second, with respect to the limited translation of sport outcomes in other life domains, a stronger involvement of the distal ecological systems [32] for supporting youth educational path outside sport should be considered. Several studies reported the benefit of a multi-stakeholder approach in sport, resulting in "economy of effort", namely, better use of resources and competencies for supporting youth [35,[45][46][47]. The multi-stakeholder approach, thus, should be intensified, especially when working with vulnerable youth.…”
Section: Discussionmentioning
confidence: 99%
“…Community sports blurs the distinction between sports and recreation (McDonald, Spaaij, & Dukic, 2019). Community sports aim to lower participation thresholds by adopting a flexible, adaptable, informal and people-oriented approach that attracts all sections of the community, regardless of the norms of elite sports (Haudenhuyse, Hayton, Parnell, Verkooijen, & Delheye, 2020). Social inclusion through recreational sports participation has become a focal point.…”
Section: Social Inclusion Through Sport and Recreationmentioning
confidence: 99%
“…The Universal Declaration of Human Rights (1948) also stipulates that "access to physical education and sport shall be ensured and guaranteed for all human beings". Access to these rights becomes an argument in context for practitioners to justify the use of sport for development and for all (inclusion) in their programs (Beutler, 2008;Burke, 2017;Haudenhuyse, Hayton, Parnell, Verkooijen & Delheye, 2020;Lambert et al, 2020).…”
Section: Sport To Respect Human Rights (Sdg16)mentioning
confidence: 99%